2018
DOI: 10.2298/abs180302019b
|View full text |Cite
|
Sign up to set email alerts
|

Identification and antibiotic resistance of Bacillus spp. isolates from natural samples

Abstract: Identification of 33 Bacillus spp. isolates from different environmental samples collected from the territory of Serbia was performed by sequencing of the 5ʹ-hypervariable section of 16S rRNA gene. Eight species were identified within four phylogenetic groups: B. pumilus, B. megaterium, B. subtilis and B. cereus. Determination of their antibiotic resistance was performed using the minimum inhibitory concentration (MIC) assay. We found that just one isolate was resistant to gentamicin, 9 were resistant to clind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
1
6
0
1
Order By: Relevance
“…The spread of antibiotic resistance genes is an increasing problem, and it is also indicated that clinically relevant resistance could be detected in nonpathogenic bacterial strains as in the case of different Bacillus spp. strains originating from natural ecosystems (Berić et al., 2018 ). The occurrence of the B. cereus group as opportunistic pathogen has been associated with vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…The spread of antibiotic resistance genes is an increasing problem, and it is also indicated that clinically relevant resistance could be detected in nonpathogenic bacterial strains as in the case of different Bacillus spp. strains originating from natural ecosystems (Berić et al., 2018 ). The occurrence of the B. cereus group as opportunistic pathogen has been associated with vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that the increased prevalence of drug-resistant bacteria has become a major public health problem [20,21]. In the current study, we studied 110 clinical isolates of Enterococcus (57 E. faecalis and 53 E. faecium).…”
Section: Discussionmentioning
confidence: 99%
“…The sources of their isolation were soil, hay, and manure. Strains' characterization and identification were performed previously [12,13]. The potential of 220 strains for their ability to tolerate heat stress (50, 60, 70 • C); tolerance to salinity by observing the growth on medium amended with various concentration of NaCl (5,7,13,15,17,20,22, and 25 % (w/v)); and drought tolerance obtained by adding 5, 10, 15, 20, 30, and 40% of poly(ethylene) glycol 6000 (PEG6000) in medium was tested.…”
Section: Bacterial Strain Selection and Characterization For Plant-gr...mentioning
confidence: 99%
“…Strains' characterization and identification were performed previously [12,13]. The potential of 220 strains for their ability to tolerate heat stress (50, 60, 70 • C); tolerance to salinity by observing the growth on medium amended with various concentration of NaCl (5,7,13,15,17,20,22, and 25 % (w/v)); and drought tolerance obtained by adding 5, 10, 15, 20, 30, and 40% of poly(ethylene) glycol 6000 (PEG6000) in medium was tested. From 220 natural bacterial isolates tested preliminarily, we selected six strains: Bacillus safensis SS-2.7, B. velezensis SS-6.4 and SS-8.2.2, B. thuringiensis SS-29.2, B. licheniformis SS-30.3, and B. paralicheniformis SS-37.5 that are able to grow at 50 • C in Luria-Bertani (LB) medium with 7% NaCl and in LB medium with 30% PEG6000.…”
Section: Bacterial Strain Selection and Characterization For Plant-gr...mentioning
confidence: 99%